The Body Shop's Preparedness for Post-Pandemic Survivability: The Participation in Society and Environmental Issues - Filda Rahmiati; Fadillah Anugrah Pertiwi (Ikatan Sarjana Komunikasi Indonesia, 2022)
The existence of the Covid-19 pandemic has dramatically changed the conditions of the beauty industry. The beauty industry is a very interactive process with people trying, testing, and smelling the product. After the lockdown is enforced, like it or not, beauty products have to change direction into online selling. Online experience, sending out free samples, re-writing product descriptions, and improving images to encourage people to buy online. Additionally, the products offered should also be products that are safe to use, naturally-derived ingredients. Theory of Social Exchange Theory is used in this research to support the value chain of The Body Shop as a corporate campaign in society and environmental issues in pandemic.This research will emphasize one of the world's beauty products with the tagline